Рослинний покрив Козарського лісового урочища на південному заході Чернігівщини - Дідик, Л.В. (Український ботанічний журнал, 2010)
Исследована растительность Козарского лесного массива. Дана характеристика ценозов основных синтаксонов растительности. В сообществах выявлены виды, занесенные в Приложение № 1 Бернской конвенции, Красную книгу Украины и список регионально редких видов Черниговской обл. Обосновывается присвоение заказнику местного значения «Козарская дача» статуса ботанического заказника общегосударственного значения. Vegetation of the Kozary (Kozarsky) Forest was investigated. Characterization of cenoses of main vegetation syntaxa is given. Species listed in Annex I of the Bern Convention, the Red Data Book of Ukraine, and the regional list of rare species are revealed in plant communities. Justifications are provided for giving the Kozarska Dacha Forest the status of the botanical preserve (zakaznik) of national significance.